2016
DOI: 10.1016/j.corsci.2016.06.018
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of magnesium alloys at elevated temperatures in air: A review

Abstract: Highlights The oxidation behaviours of Mg alloys from low to high temperatures are reviewed. Characteristics of MgO during oxidation is discussed. Mechanisms of Mg oxidation is presented. Effect of various alloying elements is analysed. AbstractThis paper reviews (i) the oxidation of Mg alloys at elevated temperatures in air; (ii) the influence of alloying elements on the oxidation of Mg alloys; and (iii) the progress in the development of oxidation-resistant Mg alloys. Low oxidation rates have been shown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
65
0
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 171 publications
(75 citation statements)
references
References 163 publications
1
65
0
9
Order By: Relevance
“…(See reviews by Gusieva et al [24], Tan et al [25], Atrens et al [26] and Taheri et al [27].) There is a greater emphasis on corrosion in aqueous conditions, rather than in the relatively dry atmospheres in this study.…”
Section: Discussionmentioning
confidence: 97%
“…(See reviews by Gusieva et al [24], Tan et al [25], Atrens et al [26] and Taheri et al [27].) There is a greater emphasis on corrosion in aqueous conditions, rather than in the relatively dry atmospheres in this study.…”
Section: Discussionmentioning
confidence: 97%
“…Figure 2a. Additionally, the existence of MgO is attributed to the preferential oxidation of Mg atoms [22,23]. It could be figured out that as the NH 4 Cl content increases from 1 to 3 g gradually, the peaks of the Mg 17 Al 12 phase in the XRD pattern became smaller and smaller, which means a continuously reduced quantity of the intermetallic layer.…”
Section: Ammonium Chloride Could Keep the Surface Of The Magnesium Almentioning
confidence: 97%
“…It is reported that [22] at the beginning of the oxidation process of magnesium alloys, a compact layer would emerge at the magnesium alloy surface, and such a dense layer could separate the diffusion source from the magnesium alloy matrix, thus the diffusion of active metal atoms and the growth of the intermetallic layer on magnesium alloy surface is interfered by a dense film as illustrated in Figure 4.…”
Section: Ammonium Chloride Could Keep the Surface Of The Magnesium Almentioning
confidence: 99%
“…[7] These together with other issues inhibit the widespread application of Mg-alloys. [8][9][10] Therefore, significant efforts have been directed to understand oxidation mechanisms in Mg-alloys and to develop practical approaches to minimize their negative effects, [11][12][13][14][15] as has been reviewed recently by Czerwinski [16] and Tan et al [17] Extensive practical methods were proposed to either retard or eliminate oxidation. These include the prevention of ignition and burning by applying a flux or protective gas during casting, [18,19] the addition of reactive elements to enhance the oxidation resistance through the formation of protective oxide films, [16,20] the application of melt cleaning techniques and innovative die filling to ensure the casting quality and mechanical properties of Mg-alloys.…”
Section: Introductionmentioning
confidence: 99%